ANALISIS KESEJAJARAN PROGRAM PENDIDIKAN MASYARAKAT DENGAN ASAS PENDIDIKAN MASYARAKAT: STUDI EVALUATIF PADA LKP KARYA PRIMA KOMPUTER - Josua Felix Tarigan; Grace Ivanka Hutasoit; Sinta Ovalia (Universitas Negeri Medan, 2025)
This study aims to analyze the level of alignment of community education programs at LKP Karya Prima Komputer with the principles of community education (Penmas). The research uses a descriptive qualitative approach with observation, in-depth interviews, and documentation. The informants consist of managers, tutors, and students who are selected purposively. Data analysis is carried out through data reduction, data presentation, and conclusion drawing with triangulation techniques to maintain data validity. The results of the study show that the program has fulfilled the principles of relevance, partnership, and sustainability well. However, aspects of community participation and democratic principles still need to be strengthened through network expansion and community involvement. Overall, the program has been aligned with Penmas principles, but optimizing social participation and community-based empowerment is still a challenge. These findings confirm the importance of continuous evaluation in improving the quality of non-formal education programs